Case Report: Double Germline Mutations in BRCA1 and MSH2 in a Patient With Mixed Serous-Endometrioid Endometrial Carcinoma - Zheng, Hong; Yuan, Mingming; Wu, Huanwen; Chen, Rongrong; Gao, Yunong (Frontiers in Medicine, 2020)
Mixed serous-endometrioid endometrial carcinoma is a type of endometrial cancer with relatively low incidence. The genetic factors contributing to the tumorigenesis of mixed carcinoma remains to be explored. Here, we report the first identification of two germline mutations in BRCA1 and MSH2 in a woman with mixed serous papillary adenocarcinoma and endometrioid carcinoma. Immunohistochemistry analysis showed loss of MSH2 and MSH6 protein expression in the endometrioid component. The patient showed partial response to tislelizumab treatment following progression on chemotherapy. Two germline mutations in BRCA1 and MSH2 may collectively promote the tumorigenesis of uterine endometrium with two distinct histological components.